Analisis Perubahan Parameter Number of Signals Averaged (NSA) Terhadap Peningkatan SNR dan Waktu Pencitraan pada MRI - Dwi Rochmayanti; Thomas Sri Widodo; Indah Soesanti (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
A study about the influence of NSA shift to SNR to identify the existence of NSA shift to SNR and scan time had performed. The study aims to determine the alteration value of SNR when NSA was changed for every number and to obtain the NSA value which has more optimum image quality. The study was performed in Telogorejo Hospital at Semarang with MR modalities AirisII Hitachi 0.3 tesla by shifting NSA from 1 to 5 in cervical vertebrae (neck) sagittal T1 weighted with spin echo sequence. The SNR of five images were calculated with Matlab tool. SNR value was obtained by measuring the ROI at body of vertebra, spinal cord area and discus intervertebra to attain the signal average value. Experiment results show that the greater the NSA, the SNR is better and scan time is longer. SNR of the organ corpus, medulla spinalis and diskus intervertebra is increases from NSA 1 to 2 is 51%. When the NSA is raised to 3, the SNR increase is 89%, for NSA 4 the SNR increase is 99%, for NSA 5 the SNR increase is 102% . To get an SNR up to 100%, the NSA 4 is used. Meanwhile, to get images with good SNR and imaging duration is not long, the NSA 3 is used.